Analysis of U-Shaped Steel Failure Characteristics in Rock Burst Roadway and Design of Stable Structure and Constant Resistance O-Shed - Lianman Xu; Jinzhu Zhang; Rixin Guo; Tianhao Li; Zhijiao Qin; Aiwen Wang; Jiquan Sheng; Yonghui Xiao; Jianqiang Chen; Kunlun Liu (Advances in Civil Engineering)
The U-shaped steel support has good surface protection and is one of the main supporting forms of the roadway under rock bursts. However, in the supporting process of roadways under rock burst, there are poor mechanical properties of lap joints, resulting in a serious decline in the anti-impact performance of U-shaped steel supports. Using a combination of laboratory experiments and theoretical analysis, we study the sliding mechanism of the U-shaped steel bracket’s overlap section bearing and find the key factors affecting the sliding performance of the overlap section. The characteristics of deformation and failure of U-shaped steel supports under impact loads are analyzed by numerical calculations. An improved method for optimizing the sliding performance of the lap section is proposed to provide theoretical support for the design of stable and constant-resistance energy-absorbing O-shed supports. The research results show that the frictional properties between the contact surfaces of the overlapped sections, especially the frictional properties between the contact surfaces of the clamp and the U-shaped steel, determine the sliding characteristics of the U-shaped steel overlapped sections, which are the key factors affecting the bearing capacity of the support. The single-point maximum bearing capacity of the U-shaped steel bracket under the uniformly distributed impact load is basically close to the maximum bearing capacity of the U-shaped steel bracket under the concentrated impact load. When the U-shaped steel bracket is uniformly loaded, its bearing capacity can be increased several times. When a gasket is added between the U-section steel and the clamping bolt in the lap section, the bearing capacity changes smoothly during the sliding process, which greatly improves the friction performance between the contact surfaces, and can greatly improve the overall bearing capacity, energy absorption, and anti-impact performance of the support structure. Based on this, a stable and constant energy-absorption O-type shed structure for the impacted underground roadway in Laohutai Mine was proposed. The field application proved that improving the sliding performance at the joint of the U-shaped steel support can effectively control the deformation of the roadway under the impact load.